Primary treatment optimization of a fish canning wastewater from a Portuguese plant - Cristovão, Raquel (2014)
A sequence with three stages was optimized as a primary treatment for wastewaters from a fish canning industry of northern Portugal. Sedimentation tests were assessed at different times. The removal of a high fraction (75%) of oil and grease (O&G) and of some (48%) total suspended solids (TSS) occurred after a settling time of 1.5h. Coagulant dosage and pH value were optimized in the coagulation/flocculation treatment using several organic and inorganic coagulants. Best removal efficiencies (99.2% O&G, 85.8% TSS and 25.2% dissolved organic carbon (DOC)) were reached using 400mg/L of FeCl3 at raw pH wastewater. DAF was also tested, optimizing chamber pressure and recycle ratio. Removals of 94% for O&G and 43% for TSS were achieved. The coupling of the latter two processes was also investigated, but no improvement of the previous results was observed. The best approach proved to be a decantation process followed by coagulation/flocculation treatment. © 2014 The Authors.